Seismic Volcanostratigraphy:The Key to Resolving the Jan Mayen Microcontinent and Iceland Plateau Rift Evolution - Blischke, Anett; Brandsdóttir, Bryndís; Stoker, Martyn S.; Gaina, Carmen; Erlendsson, Ögmundur; Tegner, Christian; Halldórsson, Sæmundur A.; Helgadóttir, Helga M.; Gautason, Bjarni; Planke, Sverre; Koppers, Anthony A.P.; Hopper, John R. (Geochemistry, Geophysics, Geosystems, 2022)
Volcanostratigraphic and igneous province mapping of the Jan Mayen microcontinent (JMMC) and Iceland Plateau Rift (IPR) region have provided new insight into the development of rift systems during breakup processes. The microcontinent's formation involved two breakup events associated with seven distinct tectono-magmatic phases (∼63–21 Ma), resulting in a fan-shaped JMMC-IPR igneous domain. Primary structural trends and anomalous magmatic activity guided initial opening (∼63–56 Ma) along a SE-NW trend from the European margin and along a WNW-ESE trend from East Greenland. The eastern margin of the microcontinent formed during the first breakup (∼55–53 Ma), with voluminous subaerial volcanism and emplacement of multiple sets of SSW–NNE-aligned seaward-dipping reflector sequences. The more gradual, second breakup (∼52–23 Ma) consisted of four northwestward migrating IPR (I–IV) rift zones along the microcontinent's southern and western margins. IPR I and II (∼52–36 Ma) migrated obliquely into East Greenland, interlinked via segments of the Iceland-Faroe Fracture Zone, in overlapping sub-aerial and sub-surface igneous formations. IPR III and IV (∼35–23 Ma) formed a wide igneous domain south and west of the microcontinent, accompanied by uplift, regional tilting, and erosion as the area moved closer to the Iceland hotspot. The proto-Kolbeinsey Ridge formed at ∼22–21 Ma and connected to the Reykjanes Ridge via the Northwest Iceland Rift Zone, near the center of the hotspot. Eastward rift transfers, toward the proto-Iceland hotspot, commenced at ∼15 Ma, marking the initiation of segmented rift zones comparable to present-day Iceland.